6 - Approche théorique des valeurs et anti- valeurs des traditions zaïroises : contribution a la recherche d’une culture de développement - Mwamba BAPUWA (Africa Development, 1982)
In this paper the author tries to conceptualize a development pro- moting culture. He does this with regard to pre-colonial culture(s) on the one hand and post-colonial culture(s) on the other. He takes a purely theoretical approach to the topic, analysing culture as being a system of values which must be identified by. referring first to a specific social system and then to a specific stage in the development of that system. He then argues that under-development is an « act of culture» for it maintains us in « serfdom » through a technological and scientific dependency, thus causing a cultural alienation of which the bureaucratic elite and the politico- administrative leaders are victims. This cultural alienation was introduced and is maintained by institutions set up in Africa by developed countries: schools and the media. In the author's opinion a development promoting culture has to establish, first and foremost, a new, integrated, liberated sys- tem of education ; and through this culture the media and cultural institu- tions should be able to serve the masses who create culture rather than the marketable cultural needs of the « nouveaux riches». It is only under such conditions that the political liberation of our populations can be maintai- nes and consolidated, for just as the exploitation of our labour force was not enough for the imperialists to keep us under a yoke, we are also going to need the support of the values in our culture to help our society start a real development... These values are the integrated nature of the Village Community and the priority of meeting the existential needs of all the community members. Mwamba BAPUWA, Chercheur à l'I.R.S. - BP. 1638, Kinshasa I, République du Zaire